Efficient Synthesis of Biodiesel Catalyzed by Chitosan-Based Catalysts - Anping Wang; Wenxuan Quan; Heng Zhang (International Journal of Chemical Engineering)
Catalysts play an important role in the preparation of biodiesel. It is of great significance to study catalysts with high efficiency, low cost, and easy preparation. Compared with the homogeneous catalyst system, the heterogeneous catalyst is easy to separate and has a better catalytic effect. In heterogeneous catalysts, supports and preparation methods have important effects on the dispersion of active centers and the overall performance of catalysts. However, the supports of existing solid catalysts have defects in porosity, structural uniformity, stability, and specific surface area, and the preparation methods cannot stabilize covalent bonds or ionic bonds to bind catalytic sites. Considering the activity, preparation method, and cost of the catalyst, biomass-based catalyst is the best choice, but the specific surface area of the biomass-based catalyst is relatively low, the distribution of active centers is uneven, and it is easy to lose. Therefore, the hybrid carrier of biomass-based catalyst and other materials can not only improve the specific surface area but also make the distribution of active centers uniform and the catalytic activity better. Based on this, we summarized the application of chitosan hybrid material catalysts in biodiesel. The preparation, advantages and disadvantages, reaction conditions, and so on of chitosan-based catalysts were mainly concerned. At the same time, exploring the effects of different types of chitosan-based catalysts on the preparation of biodiesel and exploring the process technology with high efficiency and low consumption is the focus of this paper.